A mutation of the atrial natriuretic peptide (guanylyl cyclase-A) receptor results in a constitutively hyperactive enzyme - Wedel, Barbara J. (The National Academy of Sciences of the USA, 1997)
Mutation of an invariant glutamate residue found within the catalytic domain of guanylyl cyclases resulted in a dramatic 14-fold increase in the activity of the guanylyl cyclase-A receptor. Even in the presence of Mn(2+)/Triton X-100, a treatment previously thought to yield hormone-independent and maximum cyclase activity, the mutant enzyme remained 7-fold more active; to our knowledge, this is the first example of a protein modification or of an added agent that significantly increases cyclase activity in the presence of Mn(2+)/Triton X-100. Intracellular concentrations of cGMP in cells expressing the mutant (E974A) cyclase were only marginally elevated by the addition of atrial natriuretic peptide, and in broken-cell preparations, the mutant enzyme also was relatively insensitive to ligand/regulatory nucleotide. The marked increase in cyclase activity was not due to a relief of protein kinase domain inhibition, since the point mutation caused 7- to 13-fold elevations in guanylyl cyclase-A activity when the protein kinase homology domain was deleted. The E974A mutation also altered the kinetics from positive cooperative to linear with respect to MnGTP, suggesting disruption of subunit–subunit interactions. Thus, a single point mutation within the catalytic domain of a guanylyl cyclase results in a constitutively hyperactive enzyme that is independent of protein kinase domain regulation.